2010
DOI: 10.1074/jbc.m109.069294
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Δ9-Tetrahydrocannabinol and Cannabidiol Differentially Inhibit the Lipopolysaccharide-activated NF-κB and Interferon-β/STAT Proinflammatory Pathways in BV-2 Microglial Cells

Abstract: Cannabinoids have been shown to exert anti-inflammatory activities in various in vivo and in vitro experimental models as well as ameliorate various inflammatory degenerative diseases. However, the mechanisms of these effects are not completely understood. Using the BV-2 mouse microglial cell line and lipopolysaccharide (LPS) to induce an inflammatory response, we studied the signaling pathways engaged in the anti-inflammatory effects of cannabinoids as well as their influence on the expression of several gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
225
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(263 citation statements)
references
References 71 publications
(75 reference statements)
33
225
1
4
Order By: Relevance
“…TRIB3 is known to inhibit the NF-κB pathway (50), and, furthermore, CBD has already been reported to exert its antiinflammatory actions via inhibition of the NF-κB signaling (51). Importantly, we found that CBD cotreatment indeed prevented the LPS-induced phosphorylation (hence inactivation) of the inhibitory IκBα and phosphorylation (hence activation) of the p65 (RelA) NF-κB isoform ( Figure 8B).…”
Section: Sebostatic Action Of Cbd Is Mediated By Trpv4-dependent Intesupporting
confidence: 57%
See 1 more Smart Citation
“…TRIB3 is known to inhibit the NF-κB pathway (50), and, furthermore, CBD has already been reported to exert its antiinflammatory actions via inhibition of the NF-κB signaling (51). Importantly, we found that CBD cotreatment indeed prevented the LPS-induced phosphorylation (hence inactivation) of the inhibitory IκBα and phosphorylation (hence activation) of the p65 (RelA) NF-κB isoform ( Figure 8B).…”
Section: Sebostatic Action Of Cbd Is Mediated By Trpv4-dependent Intesupporting
confidence: 57%
“…Thorough assessment of the microarray data highlighted the putative role of TRIB3, a known inhibitor of proinflammatory NF-κB signaling (50). In addition, inhibition of NF-κB signaling plays a crucial role in the development of CBDmediated antiinflammatory actions in other systems (51). RNA imediated selective gene silencing of TRIB3 in human sebocytes (Supplemental Figure 15, A and B) fully abrogated the ability of CBD to inhibit LPS-induced proinflammatory responses (Figure 8A).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that several plant-derived (i.e. phytocannabinoids) and synthetic cannabinoids possess immunomodulatory activity, prior studies have primarily focused on their effects on leukocytes and microglia without assessing their effects on the endothelium, which is known to be centrally involved in acute inflammatory disorders such as sepsis (17)(18)(19). In sepsis, the persistent, direct, and unresolved engagement of endothelial Toll-like receptors (TLRs) by microbial components, and the sustained secretion of endogenous inflammatory mediators, such as tumor necrosis factor (TNF)␣ and interleukin (IL)-1␤, lead to endothelial activation and dysfunction (20 -24).…”
mentioning
confidence: 99%
“…Végső soron a CBD 5 mg/kg/nap dózisban lymphopeniát már kiválthat, de csak a B-, T-, Tc-és Th-sejtek számának csökkenése jelentkezik, azaz a specifi kus immunválasz gyengül, míg a megfi gyelések szerint a nem specifi kus, tumorra és vírusokra adott válasz erősö-dik [35].…”
Section: áBraunclassified